2015
DOI: 10.5935/1518-0557.20150019
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Serum Anti-Müllerian Hormone Levels in Infertile Patients after Hyperbaric Oxygen (preliminary results)

Abstract: Objective: To assess whether hyperbaric oxygen sessions elevate serum levels of anti-Müllerian hormone (AMH) in patients diagnosed with infertility with serum levels of less than or equal to 1 ng/dl AMH. Methods: A study was performed on 4 patients diagnosed with infertility. Serum AMH level was measured at the beginning and end of hyperbaric oxygen sessions, and endometrial thickness was measured on endometrial cycle day 14 before and during the hyperbaric oxygen sessions. Results: In two of the four patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
3
0
2
Order By: Relevance
“…It was found that hyperbaric oxygen could effectively regulate the FSH and LH serum levels in patients, improve clinical symptoms, and shorten the course of the disease. Hyperbaric oxygen therapy for premature ovarian failure could significantly improve the positive regulation of FSH, LH, and E2 serum levels as well as relieve a series of clinical symptoms caused by premature ovarian failure ( 21 ). For patients with ovarian pedicle torsion, Svensson et al ( 22 ) found that after laparoscopic reverse torsion and hyperbaric oxygen therapy, a gradual recovery of blood supply in the ovary was confirmed by contrast-enhanced ultrasonography.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that hyperbaric oxygen could effectively regulate the FSH and LH serum levels in patients, improve clinical symptoms, and shorten the course of the disease. Hyperbaric oxygen therapy for premature ovarian failure could significantly improve the positive regulation of FSH, LH, and E2 serum levels as well as relieve a series of clinical symptoms caused by premature ovarian failure ( 21 ). For patients with ovarian pedicle torsion, Svensson et al ( 22 ) found that after laparoscopic reverse torsion and hyperbaric oxygen therapy, a gradual recovery of blood supply in the ovary was confirmed by contrast-enhanced ultrasonography.…”
Section: Discussionmentioning
confidence: 99%
“…Its experimental use for the treatment of certain types of infertility has been limited so far, although it has shown promising results 86 .…”
Section: Background Of Treatment With Hyperbaric Oxygenmentioning
confidence: 99%
“…Studies have shown that hyperbaric oxygen therapy can improve uterine hemodynamics and ER, improve ovum quality, and improve the reproductive capacity of infertile patients [ 170 , 171 ]. However, studies have shown that hyperbaric oxygen therapy did not promote endometrial thickening but increased serum AMH level, which still needs further research [ 172 ].…”
Section: Overview Of Other Cam In the Treatment Of Infertilitymentioning
confidence: 99%